Antidiabetic potential of Gaultheria trichophylla in mice (Bangladesh Journal of Pharmacology, 2017)
This study evaluated Gaultheria trichophylla for its in vitro and in vivo anti-diabetic activity and its effect on biochemical parameters. The extract inhibited ?-glucosidase with IC50 = 17.5 ± 0.1 ?g/mL). The difference of body weight of the extract-treated diabetic groups and diabetic control was significant (p